Enkele slotakkoorde oor die toekoms van die Afrikaanse gereformeerde kerke in Suid-Afrika, ook ná Covid-19 - Hofmeyr, Hoffie (Stellenbosch Theological Journal, 2021)
Some concluding perspectives on the future of the Afrikaans reformed churches, also after Covid-19 This article contains, besides the previous article on some options as related to the future of the main Afrikaans reformed churches in South Africa, some more practical perspectives on the future of these churches. While religiosity still plays an important role in South African society, many other decisive biblical and ecclesiastical factors play a role in deciding the future of the so-called established Afrikaans reformed churches. Extensive attention is given to the realities of membership decline, lack of interest in church life, diversity, unity, ecumenical relations and a new missional focus. Issues like fundamentalism and relativism in reformed theology are also briefly discussed. The major effect of the Covid-19 virus on church life is also highlighted in some greater detail and various practical issues because of Covid-19 are attended to. Though the future of these churches is calling for various adaptions, its future is not without hope.